2012
DOI: 10.1149/2.021204jes
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cu(In,Ga)Se2Films Prepared by Atmospheric Pressure Selenization of Cu-In-Ga Precursors Using Ditert-Butylselenide as Se Source

Abstract: In this study, copper indium gallium diselenide [Cu(In,Ga)Se 2 ; CIGS] films were prepared by selenization of Cu-In-Ga metallic precursors using ditert-butylselenide (DTBSe) under atmospheric pressure. Based on the results of θ-to-2θ X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM), it was found that the films selenized at 300 or 400 • C for 60 min showed the presence of Kirkendall voids along with the XRD signitures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In addition, the adhesion of CIGS to Mo back-contact is poor because of stress built-up by volume expansion 9 and void formation at the CIGS/Mo interface by out diffusion of metal atoms from the Mo surface. 10,11 As alternative Se sources, Se pellets 12,13 or metal-organic sources 14 were used instead of H 2 Se gas, but the interface void problem could not be easily solved. To avoid void formation, CIGS targets that already contained Se was employed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the adhesion of CIGS to Mo back-contact is poor because of stress built-up by volume expansion 9 and void formation at the CIGS/Mo interface by out diffusion of metal atoms from the Mo surface. 10,11 As alternative Se sources, Se pellets 12,13 or metal-organic sources 14 were used instead of H 2 Se gas, but the interface void problem could not be easily solved. To avoid void formation, CIGS targets that already contained Se was employed.…”
Section: Introductionmentioning
confidence: 99%
“…Both showed almost identical XRD patterns in good agreement with the typical CIGSSe chalcopyrite structure (JCPDS 35–1102). Binary compounds such as InSe and CuSe were not observed in the XRD patterns 29 . The Fig.…”
Section: Resultsmentioning
confidence: 93%
“…It is observed that several hundred nm-sized voids were formed near the bottom Mo/CIGS interface in an otherwise compact polycrystalline CIGS film. It has been suggested that the formation of the voids was due to the Kirkendall effect driven by the differences in the diffusivity of outward-diffusing indium, gallium, and/or copper, and that of sluggishly in-diffusing selenium during the low-temperature selenization. , However, the presence of the voids did not appear to seriously affect the operation of CIGS as a light-absorbing electrode, as confirmed by good device performance (photoconversion efficiency ∼14.7%) of solar cells based on a CIGS absorber prepared by the same batch (see Figure S2 in Supporting Information). A MoSe 2 layer with an average thickness of 40 nm was formed during the selenization, which has been known to create good ohmic contact to the CIGS and this should be beneficial for the PEC performances. , …”
Section: Resultsmentioning
confidence: 95%